The Holy Spirit and the early Church: The experience of the Spirit - van Oort, Johannes (HTS Teologiese Studies / Theological Studies, 2012)
Firstly, the present article explored the occurrence of special gifts of the Holy Spirit (charismata) both in the New Testament and in a number of early Christian writers (e.g. Justin Martyr, Irenaeus, Tertullian and Augustine). Secondly, it indicated how this experience of special charismata exerted its influence on the formulation of the most authoritative and ecumenical statement of belief, viz. the Creed of Nicaea-Constantinople (381).
Free
Keywords: BIBLE. New Testament; CHURCH; GRACE (Theology); HOLY Spirit; PENTECOSTALISM; SPIRITUAL gifts